Prevalence of rotavirus-induced diarrhea among children under 5 years in Ilorin, Nigeria - Odimayo, M S; Olanrewaju, W I; Omilabu, S A; Adegboro, Boaz (Journal of tropical pediatrics (1980), 2008)
Diarrhoea disease is an important cause of morbidity and mortality in Nigerian children and rotavirus has been identified as an important causative agent among children below 5 years. We determined the prevalence of rotavirus-induced diarrhoea among under-5 s by electrophenotyping. Stool samples were collected from eligible subjects who presented with acute diarrhoea. The samples were processed for viral studies by electrophenotyping. Among the 299 subjects recruited, 55.9% were positive for rotavirus. Eighty percent of the recruited patients were below 24 months. There was a significant decrease (p-value = 0.00001) in the prevalence of rotavirus among diarrhoea patients above the age of 24 months when compared with those below this age group. Rotavirus was associated with higher morbidity and mortality. We conclude that rotavirus is the most important cause of diarrhoea among children <5 years in Ilorin, Nigeria and its prevalence is highest in the first 2 years of life. Adequate rehydration should be regarded as the mainstay of management.